Methane measurements at lander 2 in the German Baltic Sea - Daniel Lars Pönisch; Henry C Bittig; Gregor Rehder (PANGAEA, 2025)
Coastal ecosystems are heterogeneous environments with high turnover rates of carbon and nutrients that influence the distribution of greenhouse gases (GHG). They also represent challenging environments for scientific investigations, requiring new technologies that go beyond discrete sampling. Here we present temporal high-resolution measurements of several physicochemical variables, including the partial pressures of CO2 and CH4, made in shallow waters at around 6 m water depth of the Baltic Sea using two autonomous lander systems. The two landers were deployed at the sediment-water interface (bottom lander) and about 400 m offshore near the German city Rostock with support from the buoy tender “Rosenort” operated by the Wasserstraßen- und Schifffahrtsverwaltung des Bundes, Stralsund (WSA Stralsund). These landers were equipped with six commercially available state-of-the-art sensors. Field data resolution ranged from 10 seconds to 60 minutes and was obtained for partial pressure of CO2 (Contros HydroC-CO2) and CH4 (Contros HydroC-CH4), temperature, salinity, depth (hydrostatic pressure), O2 (CTD-O2 with SBE-37SMP-ODO), the concentrations of phosphate (SBE HydroCycle PO4), nitrate (SBE SUNA V2), chlorophyll a and the turbidity (both with SBE-FLNTUSB ECO) as stationary measurements at two different locations in close proximity. The CTD and oxygen measurements provide exact water depth data for the respective lander locations. In the other data sets (e.g., CO2 measurements) rounded data is inserted instead of the exact depth data, which is 6 m for lander_1 and 5 m for lander_2. The deployment and recovery of the landers and thus the measurements took place between 04 September 2019 and 04 October 2019 and the sensors were operated under battery power and a centralized timestamp. Three events common to coasts were observed during the deployment, allowing tracking of (1) an advection of saline waters with a mineralization signal, (2) a storm event of about 4 days, and (3) a stagnation event. Sensor data and processed data are available in separate files.
In: Pönisch, DL et al. (2025): Autonomous high-resolution multi-parameter measurements of marine variables in shallow near-shore waters of the German Baltic Sea to study the variability and drivers of carbon dioxide and methane [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.956806